Online Learning Analysis of Botany Cryptogamae During the Covid-19 Pandemic - Agus Wahyuda; Aldi Suhendra; Ari Hayati Purba; Pooja Hujaibah; Miftahul Khairani (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
During the Covid-19 pandemic, online learning is a solution in the world of education, including learning carried out by Tadris Biology students at UIN Sumatera Utara. The purpose of this study was to determine the level of success in online learning Botany Cryptogamae. This research focuses on the Botany Cryptogamae course which is conducted online. Qualitative research model with data collection techniques carried out through a google form questionnaire and continued with qualitative descriptive analysis. The research subjects are Biology Tadris students who are in the Odd Semester of the 2020-2021 Academic Year who are taking the cryptogamae botany course with a total of 46 students as respondents. The results of student responses stated that online learning of Botany Cryptogamae was not going well in terms of psychology and facilities.